2020
DOI: 10.1093/ptep/ptaa115
|View full text |Cite
|
Sign up to set email alerts
|

Thundercloud Project: Exploring high-energy phenomena in thundercloud and lightning

Abstract: We designed, developed, and deployed a distributed sensor network aiming at observing high-energy ionizing radiation, primarily gamma rays, from winter thunderclouds and lightning in coastal areas of Japan. Starting in 2015, we have installed, in total, more than 15 units of ground-based detector system in Ishikawa Prefecture and Niigata Prefecture, and accumulated 551 days of observation time in four winter seasons from late 2015 to early 2019. In this period, our system recorded 51 gamma-ray radiation events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 56 publications
0
30
0
Order By: Relevance
“…One is that there is a single gamma‐ray glow that is so wide that it covers two detectors 1.35 km apart at the same time. Previous observations of gamma‐ray glows during winter thunderstorms in Japan suggested that gamma‐ray glows are moving with thunderclouds (precisely, with rainfall regions; see Torii et al., 2011; Wada, Enoto, Nakamura, et al., 2019; Yuasa et al., 2020). However, in the present case, since the ambient wind is heading from Detector A to B, Detector A should observe the gamma‐ray enhancement 110 s earlier than Detector B if the gamma‐ray glow has a small variance of the flux in time.…”
Section: Discussionmentioning
confidence: 98%
“…One is that there is a single gamma‐ray glow that is so wide that it covers two detectors 1.35 km apart at the same time. Previous observations of gamma‐ray glows during winter thunderstorms in Japan suggested that gamma‐ray glows are moving with thunderclouds (precisely, with rainfall regions; see Torii et al., 2011; Wada, Enoto, Nakamura, et al., 2019; Yuasa et al., 2020). However, in the present case, since the ambient wind is heading from Detector A to B, Detector A should observe the gamma‐ray enhancement 110 s earlier than Detector B if the gamma‐ray glow has a small variance of the flux in time.…”
Section: Discussionmentioning
confidence: 98%
“…One more high-energy phenomenon has been discovered to be associated with thunderstorms. It is often referred to as "gamma-ray glows" [5,[13][14][15][16][17][18] or "thunderstorm ground enhancements" [19,20], although no single term has been agreed on yet to describe it (see, e.g., [4,[21][22][23][24][25]). Enoto et al [25] use the term "γ-ray glow" only to describe "bremsstrahlung radiation from electrons accelerated in thunderclouds".…”
Section: Gamma-ray Glows and Secondary Emission Of High-energy Photons Due To Photonuclear Reactionsmentioning
confidence: 99%
“…They term the latter emission "prolonged line emission." The term "prolonged emission" can be considered as a universal one describing any flux of high-energy photons not associated with rain washout of radioactive isotopes (see, e.g., [15][16][17][18]20,21,23,25]), with a duration of about one second or longer.…”
Section: Gamma-ray Glows and Secondary Emission Of High-energy Photons Due To Photonuclear Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Japan, citizen science projects have been conducted in recent years, along with intelligent devices and network communication technologies. One recent and successful example involving particle measurements is the Thundercloud project [4] to observe gamma rays generated in thunderclouds. In these cases, scintillation detectors are provided by scientists and installed in schools for observation together with students.…”
Section: Introductionmentioning
confidence: 99%